2016
DOI: 10.1093/neuonc/now178
|View full text |Cite
|
Sign up to set email alerts
|

Primary intramedullary spinal cord lymphoma: a population-based study

Abstract: Background. Primary intramedullary spinal cord lymphoma (PISCL) is a rare diagnosis with poorly understood disease progression. Clarification of the factors associated with survival in PISCL patients is warranted. Methods. We conducted a population-based cohort study utilizing prospectively collected data from the Surveillance, Epidemiology, and End Results (SEER) database. Patients with histological diagnosis of primary lymphoma in spinal cord (C72.0) from 1973 to 2012 in the SEER database were included. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…13 Also, family support may increase compliance or adherence to cancer-related therapy. [14][15][16][17] In the present study, we observed the negative effect of separated/divorced/widowed status on the outcome of patients with SmCC of the salivary gland in univariate Cox survival analysis, but without statistical significance after adjusting for other confounding factors. The association of marital status and survival is required to be explored in a large cohort of patients in the future.…”
Section: Discussionmentioning
confidence: 56%
“…13 Also, family support may increase compliance or adherence to cancer-related therapy. [14][15][16][17] In the present study, we observed the negative effect of separated/divorced/widowed status on the outcome of patients with SmCC of the salivary gland in univariate Cox survival analysis, but without statistical significance after adjusting for other confounding factors. The association of marital status and survival is required to be explored in a large cohort of patients in the future.…”
Section: Discussionmentioning
confidence: 56%
“…Intramedullary lymphoma with spinal cord involvement is rare, accounting for 1% of PCNSL (5). The average age of the disease was 50 years, with a higher prevalence being observed in men and 50-60 years being the peak period of incidence (6). The clinical symptoms of primary intramedullary spinal cord lymphoma are usually non-speci c and related to the levels of the spinal cord involvement (7).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al conducted a population-based study of 346 PISCL patients using the Surveillance, Epidemiology, and End Results (SEER) database. They found that the clinicopathologic factors age, marital status, race, tumor stage, tumor histology, and year of diagnosis were correlated with PISCL patient survival outcome [30]. However, there has been no study developing a clinical nomogram for PISCL patient prognosis.…”
Section: Introductionmentioning
confidence: 99%